Late-stage alteration and tin–tungsten mineralization in the Khuntan Batholith, northern Thailand - Yokart, B; Barr, S.M; Williams-Jones, A.E; Macdonald, A.S (Journal of Asian earth sciences, 2003)
The Khuntan Batholith is part of the Triassic–Jurassic eastern marginal belt of the Northern Thailand Granite Province. Most of the batholith consists of coarse-grained, porphyritic to megacrystic biotite–muscovite granite (Huai Mae San unit). However, the southeastern part, called the Muang Yao unit, consists of coarse- to medium-grained muscovite and muscovite–tourmaline granite and is associated with Sn–W mineralization. The Huai Mae San granite has S-type petrological features typical of batholiths in the eastern marginal belt, which formed in a syn-collisional setting. The more silicic Muang Yao granite differs chemically from felsic S-type granite, for example in extreme Rb–Y–Nb enrichment and Ba–Sr–Zr depletion, probably as a result of late-stage fluid alteration. Vein-hosted deposits of cassiterite, scheelite, and wolframite associated with minor sulfides occur in both the Muang Yao granite and adjacent metamorphic rocks. Fluid-inclusion studies indicate that both aqueous and aqueous-carbonic fluids of low salinity (0–8 wt% equiv. NaCl) were involved in vein formation, and were subject to pressure fluctuation between essentially lithostatic and hydrostatic conditions. Dilution of magmatic hydrous fluid by influx of meteoric water may explain the anomalously low salinity. Oxygen isotope data support a primary magmatic origin for the fluid, and indicate temperatures of ca. 400 °C for ore deposition. The three vein-type Sn–W deposits of this study represent a spectrum from an endogranite vein system to proximal-intermediate vein systems of magmatic-hydrothermal origin.